Representasi Identitas Muslimah dalam Iklan Televisi Sunsilk, Wardah dan Emeron - Adhitya Prasetyo; Fajar Junaedi (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2020)
As an Islamic majority country, various Islamic attributes (including muslimah) are often used as a seasoning for the promotion of advertising through representation. However, advertising does not represent a reality as a whole because the representation that appears in an advertisement is the result of the construction between the reality and the ideas of advertisers. Various signs that represent muslimah in an advertisement become a standard of idealization and build an identity for muslimah. Identity can be easily interpreted through the signs of tastes, beliefs, attitudes and lifestyles. This research tries to see how muslimah identity is represented by the following television advertisements Sunsilk's television commercial version "Hijab Refresh - Laudya Cynthia Bella", Wardah ad version "Exclusive Series - #FeelThePerfection", and Emeron ad version "Apapun Style Hijabmu, Perawatan Rambutnya Emeron Hijab Shampo". This thesis research uses the Roland Barthes semiotics method with data collection techniques in the form of documentation and literature study. Through the three existing research objects, the author sees that advertisements represent muslimah identity through several things, including trends in hijab fashion on muslimah, actions taken by muslimah as an expression of their interest in popular culture and cultural hybridization that occurs in muslimah. These three points are conveyed by advertisements through the signs in the advertisements and build values that represent muslimah.